Attitudes and Beliefs towards Patients with Hazardous Alcohol Use: A Systematic Review. (28th November 2012) - Mabood, Neelam; Zhou, Hansen; Dong, Kathryn A.; Ali, Samina; Wild, T. Cameron; Newton, Amanda S.
Abstract : Objective . To describe emergency department (ED) staff attitudes and beliefs towards patients presenting with hazardous alcohol use and their clinical management. Methods . A search of MEDLINE, EMBASE, CINAHL, SCOPUS from 1990 to 2010, and reference lists from included studies was conducted. Two reviewers independently screened for inclusion and assessed study quality. One reviewer extracted the data and a second checked for completeness and accuracy. Results . Among nine studies four reported varied beliefs on whether screening was worthwhile for identifying hazardous alcohol use (physicians: 42%–88%; nurses: 50%–100%). Physicians in three studies were divided on intervention provision (32%–54% in support of intervention provision) as were nurses in two studies (39% and 64% nurses in support of intervention provision). Referral for treatment was identified in two studies as an important part of ED management (physicians: 62% and 97%; nurses: 95%). Other attitudes and beliefs identified across the studies included concern that asking about alcohol consumption would be seen as obtrusive or offensive, and a perceived lack of time and resources available for providing care and referrals. Conclusions . ED staff had varying attitudes towards ED management of patients with hazardous alcohol use. Investigations into improving clinical care for hazardous alcohol use are needed to optimize ED management for these patients.